Under the lilacs - Alcott, Louisa May, 1832-1888. (Boston : Little, Brown, 1996)
Relates the adventures of Ben Brown, his performing poodle Sancho, and the two young girls who feed and care for them after the boy and dog run away from the circus.
"From the original publisher."
Keywords: Runaways -- Fiction; Dogs -- Fiction; Friendship -- Fiction